Older people with diabetes – avoiding hospitalization. (July 2015) - Abdelhafiz, Ahmed H; Russell, Joanne J; Key, Andrew; Sinclair, Alan J
SUMMARY : Diabetes phenotype in old age is characterized by increased prevalence of co-morbidities, geriatric syndromes and frailty. Interaction between geriatric syndromes and diabetes will have a synergistic effect to worsen adverse outcomes such as increased vascular complications, disability and hospitalization. Risk factors for hospitalizations include hypoglycemia, poor glycemic control, infections and acute exacerbation of the associated co-morbidities or geriatric syndromes. A large proportion of hospitalizations are preventable. Integrated care system between primary and secondary care to provide a holistic care for older people with diabetes with a focus on early and effective interventions, maintaining functional status and autonomy and promoting a good quality of life and well-being for each patient are warranted as part of any strategy to reduce hospitalization.